2021
DOI: 10.1037/cfp0000175
|View full text |Cite
|
Sign up to set email alerts
|

Clinically significant depression among parents during the COVID-19 pandemic: Examining the protective role of family relationships.

Abstract: Responding to families at heightened risk for mental health burdens during the COVID-19 pandemic is critical-evidence suggests parents face elevated burdens compared to their nonparent counterparts. Building on studies that demonstrate a spillover of stress across domains and individuals within families, this study examines longitudinal predictors of elevated risks for clinical depression among parents based on relational family indicators, COVID-specific stressors, and stress and emotion regulation indicators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…For example, conflict about co-parenting was positively related to parent’s reports of depression and worry and was negatively linked to parent’s relationship quality during adjustment to the pandemic ( Feinberg et al, 2021 ). Parents not classified as clinically depressed during the first 7 weeks of the pandemic had closer relationships with their children in that period than did clinically depressed parents ( Russell et al, 2021 ). Parental burnout increased from 2018 to during the lockdown, with mothers reporting higher levels of burnout than fathers in a Portuguese study ( Aguiar et al, 2021 ).…”
Section: Review and Synthesis Of The Literaturementioning
confidence: 99%
“…For example, conflict about co-parenting was positively related to parent’s reports of depression and worry and was negatively linked to parent’s relationship quality during adjustment to the pandemic ( Feinberg et al, 2021 ). Parents not classified as clinically depressed during the first 7 weeks of the pandemic had closer relationships with their children in that period than did clinically depressed parents ( Russell et al, 2021 ). Parental burnout increased from 2018 to during the lockdown, with mothers reporting higher levels of burnout than fathers in a Portuguese study ( Aguiar et al, 2021 ).…”
Section: Review and Synthesis Of The Literaturementioning
confidence: 99%
“…Research has found that children's stress‐related symptoms may be buffered by positive and responsive parenting (Masten, 2001 ). Positive and responsive parenting includes active and supportive coping strategies (i.e., coaching children on how to handle stressful situations by encouraging verbalization of feelings, modeling appropriate emotions when tackling problems); positive family environment (i.e., communication, affection, mutual respect, spending quality time together); and high‐quality parent–child relationships, which are correlated with high levels of coping in children (Kliewer et al, 1996 ; Russell et al, 2021 ). In contrast, child outcomes after a crisis, including heightened levels of stress, are worsened for the children of highly distressed parents (Prime et al, 2020 ).…”
Section: Family Relationships Under Stressmentioning
confidence: 99%
“…Further, parents' mental health symptoms may interfere with parents' perceptions of their children's stress, as seen in depressed and anxious mothers' overreporting of their children's psychiatric symptoms [42], and in withdrawn or unavailable patterns of parent-child interaction [43][44][45]. Adding an additional risk consideration is the presence of pre-existing mental health symptoms that may hamper parents' abilities to leverage the necessary resources to be resilient to the challenges presented by COVID-19, including coping with the strains of caregiver burden [46].…”
Section: Parent Mental Health and Caregiving During A Crisismentioning
confidence: 99%